Importance of Immediate Thiamine Therapy in Children with Suspected Thiamine-Responsive Megaloblastic Anemia—Report on Two Patients Carrying a Novel SLC19A2 Gene Mutation - Spehar Uroic, Anita; Milenkovic, Dragan; De Franco, Elisa; Bilic, Ernest; Rojnic Putarek, Natasa; Krnic, Nevena (Journal of Pediatric Genetics, 2020)
Thiamine-responsive megaloblastic anemia (TRMA) is an autosomal recessive disorder characterized by the development of megaloblastic anemia, diabetes mellitus, and sensorineural deafness. We report on the first two Croatian patients with TRMA, compound heterozygotes for nonsense, c.373C > T; p.(Gln125Ter) and novel missense variant, c.1214C > G; p.(Thr405Arg) in SLC19A2 gene. The first was diagnosed at 4 months with diabetes mellitus and severe anemia requiring transfusions. As TRMA was suspected, thiamine therapy was immediately started to prevent further transfusions and insulin therapy. His brother developed extreme anemia at 3 weeks of age while waiting for the results of the genetic test. Severe anemia in this sibling may have been prevented if thiamine had been initiated earlier.
Keywords: thiamine-responsive megaloblastic anemia; neonatal diabetes mellitus; SLC19A2 gene